2019
DOI: 10.7554/elife.48408
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional diversity of midbrain dopamine neurons within identified axonal projections

Abstract: Functional diversity of midbrain dopamine (DA) neurons ranges across multiple scales, from differences in intrinsic properties and connectivity to selective task engagement in behaving animals. Distinct in vitro biophysical features of DA neurons have been associated with different axonal projection targets. However, it is unknown how this translates to different firing patterns of projection-defined DA subpopulations in the intact brain. We combined retrograde tracing with single-unit recording and labelling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 82 publications
7
94
2
Order By: Relevance
“…In vivo patch-clamping enabled the systematic investigation of subthreshold signatures underlying tonic and phasic firing patterns in the intact brain. We found that a majority of neurons fired in a single spiking pattern, similar to our previous in vivo extracellular studies of identified dopamine neurons (Farassat et al, 2019;Schiemann et al, 2012). A representative recording and the immunohistochemistry of an in vivo pacemaking dopamine neuron located in the VTA is shown in Figures 2AB.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In vivo patch-clamping enabled the systematic investigation of subthreshold signatures underlying tonic and phasic firing patterns in the intact brain. We found that a majority of neurons fired in a single spiking pattern, similar to our previous in vivo extracellular studies of identified dopamine neurons (Farassat et al, 2019;Schiemann et al, 2012). A representative recording and the immunohistochemistry of an in vivo pacemaking dopamine neuron located in the VTA is shown in Figures 2AB.…”
Section: Resultssupporting
confidence: 86%
“…Upon further investigation of the subthreshold signatures underlying tonic and phasic firing patterns in vivo, we found that a majority of neurons fired in a single spiking pattern, similar to our previous in vivo extracellular studies of identified dopamine neurons (Farassat et al, 2019;Schiemann et al, 2012). While there is some variability in the subthreshold membrane minima as compared to the maxima, the respective ISIs of both plots show the high degree of steady spiking in pacemaking dopamine neurons.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Past studies have classified substantia nigra dopamine neurons subpopulations according to their projection targets (Farassat et al, 2019;Lerner et al, 2015;Schiemann et al, 2012), expression of neurochemical markers (La Manno et al, 2016;Poulin et al, 2018;Wu et al, 2019), and intrinsic membrane properties Neuhoff et al, 2002). Based on the anatomical results, Crittenden et al (2016) proposed that dopamine neuron clusters (in bouquets) may form specialized nigral compartments.…”
Section: Defining Snc Dopamine Neuron Subpopulationsmentioning
confidence: 99%